Automated algebraic calculation of interactively constructed geometric figures — a didactic analysis - Schumann, Heinz (Computer Tools in Education, 2017)
Ordinary interactive dynamic geometry systems (IDGS) cannot generally show, how a measurable property of an interactively constructed geometric figure depends on the determining variables of that figure. With a certain method of “Automated Deduction in Geometry” (ADG), implemented in Geometry Expressions (abbreviated GX, homepage: http://www.geometryexpressions.com/), it is now possible to calculate such a dependency as an algebraic expression consisting of the determining variables. We explain this facility by selected examples, which represent the usage of this tool and evaluate its application in classroom. keywords planimetry, automated calculation, interactive dynamic geometry systems.